Pemberdayaan Masyarakat Melalui Implementasi IoT pada Sistem Penyiraman Otomatis Berkelanjutan - Waluyo, Bambang Suhardi; Effendi, Yafid; Rosyidin, Ali; Fattah, Fanni; Efrizal, Efrizal (Universitas Muhammadiyah Tangerang, 2024)
The rapid development of Internet of Things (IoT) technology has significantly transformed various sectors, including smart irrigation systems for residential and agricultural applications. This community engagement program aims to introduce and implement an automated irrigation system based on IoT to enhance water efficiency and reduce manual labor in plant care. The program was conducted in Manis Jaya, Tangerang, involving local youth and community members through seminars and hands-on workshops. The results showed that 80% of participants demonstrated an improved understanding of IoT technology, and a majority expressed willingness to adopt the system in their households. Additionally, the automated irrigation system reduced water consumption by 25–30% compared to manual methods, demonstrating its effectiveness in sustainable water management. This study highlights the potential of IoT-driven smart agriculture in urban environments, providing data-driven irrigation solutions to optimize water usage. Future developments should focus on integrating Artificial Intelligence (AI) for predictive irrigation based on environmental conditions and expanding public training programs for broader adoption. This initiative contributes to enhancing digital literacy, water conservation, and sustainable urban agriculture through accessible technological innovation.